Municipal solid waste compost as a growing media component in combination with fertilizers for the marigold seedlings production - Tzortzakis, Nikos G.; Papadaki, Anastasia; Chrysargyris, Antonios (My University, 2021)
Municipal solid waste compost (MSWC) has been recently used in agriculture. The present study investigated the effects of supplementary nutrient in the production of marigold (Tagetes erecta L.) replacing part of the peat in the growing media with MSWC. Extracts (10-0 up to 10-6 dilutions) of MSWC evaluated for seed priming/germination in Petri dishes. The MSWC extracts at 10-1-10-6 accelerated seedling germination, shoot and root radicle length. Under nursery conditions, two growing media [peat:MSWC (85:15); peat:MSWC (55:45)] were prepared from commercial peat (P) and MSWC, and nutrients applied as basic fertilizer (BF) or hydro fertilizer (HF). Seedling growth/development parameters were assessed. Seed emergence accelerated when HF nutrients added in low MSWC content while both nutrients application (BF and HF) affected negatively seed emergence and mean emergence time. Seedlings grown in mixtures with high MSWC content displayed worse quality and suitability for transplanting while seedlings growing in 15% MSWC content did not differ (in terms of seedling height, leaf number, fresh weight) compared with the equivalent control. Indeed, in some cases 15% MSWC accelerated seedlings stem diameter, Chlorophyll b, K and P content but decreased total carotenoids and dry mater content compared to the control treatment. Thus, low content (15%) of MSWC can replace peat partially with more positive effects if nutrients provided through HF rather than BF.
Keywords: Compost; Municipal solid wastes; Peat; Growth; Fertigation; Marigold; Seed emergence